Lipids, lipoprotein distribution and nutritional parameters over the ramadan period in hemodialysis patients - Tashkandi, Bayan; Kaur, Deepinder; Latifi, Eno; Tallman, Dina A; Chinna, Karuthan; Mat Daud, Zulfitri 'Azuan; Karupaiah, Tilakavati; Alhozali, Hanadi; Khosla, Pramod (Multidisciplinary Digital Publishing Institute, 2019)
The period of Ramadan (R) is associated with dramatic changes in eating habits involving extended periods of fasting on a daily basis. The current study assessed whether lipids and lipoproteins were impacted during R in chronic hemodialysis (HD) patients. Forty-five subjects in an outpatient dialysis clinic in Saudi Arabia were evaluated for anthropometric and lipid changes on a monthly basis before, during as well as one and two months after R. In addition to routine biochemical measures, anthropometric assessments including hand-grip strength (HGS), mid-arm muscle circumference (MAMC), plasma lipids and lipoproteins were evaluated. Dietary assessment was carried out using 24 h recalls. Over the course of the study, changes in renal-related parameters (creatinine, albumin, Kt/V) were minor, as were changes in plasma lipids. Large high-density lipoproteins (HDLs) and low-density lipoproteins (LDLs) accounted for the majority of their respective lipoproteins and their proportions did not change over the study period. Mean LDL particle diameters were higher during the R period, but the changes over the study period were small. Calorie intake during R (2139 ± 709 kcal/d) was significantly higher than the value noted two month post-R (1755 ± 424 kcal/d) and this was associated with significant increases in protein (69 ± 24 vs. 60 ± 24 g/d) and fat (97 ± 38, vs. 73 ± 35 g/d), respectively. No changes were noted with respect to HGS and MAMC. These data show that for HD patients, the period of R results in temporal or non-significant effects on plasma lipids, despite changes in nutrient intake.